BIOPSAR study: ultrasound-guided pre-operative biopsy to assess histology of sarcoma-suspicious uterine tumors: a new study protocol. Issue 11 (29th November 2021) - Petousis, Stamatios; Croce, Sabrina; Kind, Michel; Margioula-Siarkou, Chrysoula; Babin, Guillame; Lalet, Caroline; Querleu, Dennis; Floquet, Anne; Pulido, Marina; Guyon, Frederic
Abstract : Background: The pre-operative differential diagnosis between a uterine leiomyoma and a sarcoma can be a challenge. Available diagnostic tools have difficulty distinguishing between the two pathologies. Primary Objective: Τo evaluate the possibility of a pre-operative pathological diagnosis of atypical uterine muscle tumors by vaginal ultrasound-guided biopsy (VUGB). Study Hypothesis: Diagnostic performance of ultrasound-guided biopsy will be capable of differentiating a leiomyoma from a sarcoma with a sensitivity of >90%. Trial Design: A prospective multi-center interventional study will be performed at 10 tertiary French centers. Vaginal ultrasound Doppler examination and pelvic magnetic resonance imaging will be performed before surgery. VUGB will then be performed by a specialist radiologist. The biopsy will be obtained by performing transvaginal ultrasound under local anesthesia with lidocaine using a 16G needle. At least 4–5 specimens will be obtained in order to provide a histopathological diagnosis. All patients included in the study will be operated by laparotomy. All patients included in the study will be followed up for the subsequent 3 years according to their pathological results. Major Inclusion/Exclusion Criteria: All patients >35 years old diagnosed with a suspicious uterine tumor will be included. Primary Endpoint: Sensitivity of VUGB on pathological diagnosis. Sample Size: Considering a sensitivity of 90% (H0) as acceptable and a sensitivity of 95% (H1) as excellent, a sample size of 250 evaluable patients will be necessary to achieve 80% statistical power with a 5% type 1 statistical error. Estimated Dates for Completing Accrual and Presenting Results: Accrual will be completed in December 2024 with results presented in December 2029. Trial Registration: Institutional Review Board (Ethic Committee of Paris Ile de France 6) no 2018-A02343-52.